2017
DOI: 10.1002/hed.24930
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of selected microRNAs in sinonasal carcinoma: Value of miR‐21 as prognostic biomarker in sinonasal squamous cell carcinoma

Abstract: Background Tumors occurring in the sinonasal area are characterized by unfavorable outcome due to difficult diagnosis, treatment, and prognosis of the disease corresponding with the anatomic complexity of the area. Methods We used quantitative real‐time polymerase chain reaction (PCR) to compare relative expression of miR‐21, miR‐141, and miR‐200c in 70 formalin‐fixed, paraffin‐embedded samples of sinonasal carcinoma tissue (majority of squamous cell carcinoma [SCC] samples) with 17 control samples of sinonasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…MiRNAs affect various biological processes including carcinogenesis (11). Expression of miRNAs is tissue specific and varies between cancer and normal cells and also among different types of cancers (5,(12)(13). Deregulation of miRNAs expression has been described in a variety of tumors including pancreas, lung, breast and sinonasal tract (6,(12)(13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…MiRNAs affect various biological processes including carcinogenesis (11). Expression of miRNAs is tissue specific and varies between cancer and normal cells and also among different types of cancers (5,(12)(13). Deregulation of miRNAs expression has been described in a variety of tumors including pancreas, lung, breast and sinonasal tract (6,(12)(13).…”
mentioning
confidence: 99%
“…Expression of miRNAs is tissue specific and varies between cancer and normal cells and also among different types of cancers (5,(12)(13). Deregulation of miRNAs expression has been described in a variety of tumors including pancreas, lung, breast and sinonasal tract (6,(12)(13). Alterations in miRNAs expression have been also described in thyroid tumors including PTC (14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…For example, serum miR-378 has been suggested to be a noninvasive diagnostic biomarker for early detection of gastric cancer [23]. Kovarikova et al [24] reported significantly upregulated miR-21 in sinonasal cancer tissue and sinonasal carcinoma patients and impaired survival of the patients with a high expression level of miR-21, suggesting that miR-21 could act as a valuable prognostic biomarker. Along with these clues, we investigated which of the differently expressed miRNAs in SNIP tissue could be used as diagnostic biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Lopez and co-workers' classification of subtype based on specific marker expression and copy number alterations demonstrated that SNECs typically stain positive for both cytokeratin and neuroendocrine markers, in contrast to SNUCs and ONBs and exhibit many copy number alterations with a high level of chromosomal instability [54]. In another study assessing the status of MiR-21 as a potential prognostic marker, the authors found that the marker was upregulated in their tumour cohort, which consisted of a small minority of SNECs [55]. An important limitation of these studies is that the authors did not separate SNEC into its small and large cell entities.…”
Section: Novel Biomarkers In Sinonasal Neuroendocrine Carcinomamentioning
confidence: 98%